Design of a Neurally Plausible Model of Fear Learning - Krasne, Franklin B.; Fanselow, Michael; Zelikowsky, Moriel (Frontiers in Behavioral Neuroscience, 2011)
A neurally oriented conceptual and computational model of fear conditioning ("Fraidy Rat" or FRAT) has been constructed that accounts for many aspects of delay and context conditioning. Conditioning and extinction are the result of neuromodulation-controlled LTP at synapses of thalamic, cortical, and hippocampal afferents on principal cells and inhibitory interneurons of lateral and basal amygdala. The phenomena accounted for by the model (and simulated by the computational version) include conditioning, secondary reinforcement, blocking, the immediate shock deficit, extinction, renewal, and a range of empirically valid effects of pre- and post-training ablation or inactivation of hippocampus or amygdala nuclei.